Utilization of robusta coffee bean extract (Coffea canephora) as an alternative herbal in applied dentistry - Muhammad Dani Anko Putra; Putri Namira Zahrani; Sherly Giovani Pang; Fahmida Amira Hapsari; Ratri Maya SItalaksmi (Indonesian Journal of Prosthodontic, 2024)
Background: Indonesia is a major producer of Robusta coffee, which has variations in chemical qualities such as caffeine, polyphenols, flavonoid compounds, tannins, alkaloids, and chlorogenic acid. Research shows that Robusta coffee bean extract has potential in dental applications. The importance of Robusta coffee as an agricultural commodity and source of active ingredients with health benefits, especially in dental care. Objectives: This literature review aims to evaluate the effectiveness of Robusta coffee as oral herbal medicine. An electronic search was carried out on PubMed, Science Direct, and Google Scholar with manual search from 2018 to 2024 following the PRISMA 2020 guidelines. The review incorporated studies related to the utilization of Robusta coffee bean extract that can be applicable for oral health care. Conclusion: Robusta coffee bean extract has significant potential as an active material in dental health care, with clear antibacterial, antioxidant, and wound-healing abilities. Robusta coffee bean extract-based products as oral herbal medicine can give significant advantages to oral health. Further research is needed to optimize its use in health products.